1997
DOI: 10.3109/00365549709035869
|View full text |Cite
|
Sign up to set email alerts
|

Coinfection and Superinfection of Hepatitis B Virus in Patients Infected with Human Immunodeficiency Virus: No Evidence of Faster Progression to AIDS

Abstract: The influence of hepatitis B virus (HBV) on the natural history of human immunodeficiency virus (HIV) infection was evaluated in a prospective study of 347 HIV-positive, AIDS-free individuals infected through injecting drug use and sex and with known seroconversion dates. End points were CD4+ cell count < 200 x 10(6) cell/L and AIDS diagnosis. At entry, 229 had seromarkers to HBV; during the study, 107 had a CD4+ cell count < 200 x 10(6) cells/L and 66 developed AIDS. HBsAg chronic carriers, HBV infection-free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
39
0
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 19 publications
4
39
0
2
Order By: Relevance
“…We think this is an unlikely explanation for the absence of HBV-specific CD4 ϩ T cells in HIV-1-HBV coinfection, given that robust restoration of CD4 ϩ T cells to other organisms such as cytomegalovirus occurs following ART (3,65). Nevertheless, HIV-1 coinfection impairs the generation of HBV-specific CD4 ϩ T-cell responses and may account for the increased risk of a persistent HBV infection when HBV infection occurs following HIV-1 infection (32,62). Previous studies of chronic lymphocytic choriomeningitis virus infections show that CD4 ϩ T-cell help is essential in maintaining CD8…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We think this is an unlikely explanation for the absence of HBV-specific CD4 ϩ T cells in HIV-1-HBV coinfection, given that robust restoration of CD4 ϩ T cells to other organisms such as cytomegalovirus occurs following ART (3,65). Nevertheless, HIV-1 coinfection impairs the generation of HBV-specific CD4 ϩ T-cell responses and may account for the increased risk of a persistent HBV infection when HBV infection occurs following HIV-1 infection (32,62). Previous studies of chronic lymphocytic choriomeningitis virus infections show that CD4 ϩ T-cell help is essential in maintaining CD8…”
Section: Discussionmentioning
confidence: 99%
“…Spontaneous flares and HBeAg seroconversion occur in 5% of HBV-monoinfected individuals; however, in the setting of HIV-1-HBV coinfection, spontaneous flares or seroconversion to HBeAg is rare (18). In individuals infected with HIV-1 who subsequently acquire HBV infection, there is an increased risk of persistent chronic infection (32,62). On the other hand, HBV does not appear to have a significant impact on AIDS progression or the rate of CD4 ϩ T-cell loss (41,62).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Among the herpesviruses, epidemiological evidence confirms that CMV coinfection is associated with reduced survival (294,312,315). Furthermore, a meta-analysis of studies of acyclovir prophylaxis of HSV infection indicates that prevention of HSV infection or reactivation of HSV latent infection leads to improved survival of persons with HIV-1 infection (164).…”
Section: Impact Of Chronic Viral Coinfectionsmentioning
confidence: 99%
“…In addition, different ethnic groups may have different opportunities to access medical care [8]. Other factors, such as hepatitis coinfections and centre of care, may influence patients' immuno-virological outcomes, although previous studies have reported conflicting results, both in the precART and in the cART eras [9][10][11][12][13][14][15]. Social and clinical centre-related factors were found to be associated with the level of adherence to cART in previous studies [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%